MEMANFAATKAN MEDIA CANVA UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SENI BUDAYA PADA PESERTA DIDIK KELAS X UPWDI SMKN 2 DENPASAR - I Ketut Muada; Dina Pujipebrianti Lestari (CV. ADIBA AISHA AMIRA, 2025)
This article discusses the use of Canva media as a tool in conducting Classroom Action Research (PTK) which aims to increase interest and results in learning arts and culture in class X UPW students at SMKN 2 Denpasar. The research method used is PTK with two cycles. The research subjects were 35 students of class X UPW. Data was collected through learning achievement tests and student learning interest questionnaires. Data analysis was performed using quantitative descriptive techniques. The results of the study show that the use of Canva media can increase the interest and results of learning arts and culture in class X UPW students at SMKN 2 Denpasar. In the first cycle, the average score of the cultural arts learning outcomes test was 73.6 with a learning completeness percentage of 63.3%. Whereas in the second cycle, the average score of the learning outcomes test increased to 83.6 with a learning completeness percentage of 90%. In addition, there was an increase in students' interest in learning from 70% in the first cycle to 90% in the second cycle. Thus, it can be concluded that the use of Canva media can increase the interest and results of learning arts and culture in class X UPW students at SMKN 2 Denpasar.